2008
DOI: 10.1890/07-1328.1
|View full text |Cite
|
Sign up to set email alerts
|

Managing Trade‐offs in Landscape Restoration and Revegetation Projects

Abstract: 1Landscape restoration projects often have multiple and disparate conservation, resource 2 enhancement and sometimes economic objectives, since projects that seek to meet more than one 3 objective tend to be viewed more positively by funding agencies and the community. The degree 4 to which there are tradeoffs among desired objectives is an important variable for decision-makers, 5 yet this is rarely explicitly considered. In particular, the existence of ecological thresholds has 6 important implications for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 45 publications
0
25
0
1
Order By: Relevance
“…Similarly, Haines-Yong et al (2012) confirmed a trade-off between the provisioning services ("crop-based production") and regulating services ("habitat diver-sity"). Also, during the process of ecological restoration, which converted the agricultural land back into natural ecosystems, trade-offs can be found among different ecosystem services, such as trade-off between biodiversity and salinity mitigation (Maron and Cockfield, 2008), between carbon sequestration and species conservation , food production (Paterson and Bryan, 2012), and water supply (Chisholm, 2010). While, as humans play a critical role in managing the agroecosystem, political practices, socioeconomic incentives and technological progresses are likely to influence the quantity and quality of ecosystem services, which will further affect the direction of trade-offs (Nelson et al, 2009).…”
Section: Trade-offs In Ecosystemsmentioning
confidence: 99%
“…Similarly, Haines-Yong et al (2012) confirmed a trade-off between the provisioning services ("crop-based production") and regulating services ("habitat diver-sity"). Also, during the process of ecological restoration, which converted the agricultural land back into natural ecosystems, trade-offs can be found among different ecosystem services, such as trade-off between biodiversity and salinity mitigation (Maron and Cockfield, 2008), between carbon sequestration and species conservation , food production (Paterson and Bryan, 2012), and water supply (Chisholm, 2010). While, as humans play a critical role in managing the agroecosystem, political practices, socioeconomic incentives and technological progresses are likely to influence the quantity and quality of ecosystem services, which will further affect the direction of trade-offs (Nelson et al, 2009).…”
Section: Trade-offs In Ecosystemsmentioning
confidence: 99%
“…In a broader sense, trade-off also refers to unidirectional changes with uneven paces or rates in ESs. Trade-off analysis is a method used to explore the interactions, trends, and drivers of multiple ESs, which is helpful for an in-depth understanding of the mechanisms and ecosystem dynamics toward the establishment of adaptive management (Rodríguez et al 2006;Maron and Cockfield 2008;Bennett et al 2009;Raudsepp-Hearnea et al 2010). Due to the increased awareness and concern regarding trade-offs among ESs, trade-off analysis has emerged as a new research field in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The limited restoration resources necessitate the identification of cost effective actions and selection of restoration areas which provide multiple restoration benefits (Crossman and Bryan 2009). Planning of a large-scale restoration project can be a challenging undertaking given multiple habitats with varying degrees of degradation, multiple restoration activity choices and (often competing) priorities for ecological and socio-economic goals to be achieved within limited restoration budgets (Maron and Cockfield 2008;Turpie et al 2008;Brancalion et al 2014;Vogler et al 2015). Socio-economic co-benefits are increasingly recognized in restoration projects, because they influence restoration success (Perring et al 2015).…”
Section: Introductionmentioning
confidence: 99%